Surface association and uptake of poly(lactic-co-glycolic) acid nanoparticles by Aspergillus flavus. (November 2014) - Muse, Erica S; Patel, Nipur R; Astete, Carlos E; Damann, Kenneth E; Sabliov, Cristina M
Aim: To study the interaction of fluorescently tagged nanoparticles with Aspergillus flavus .Materials & methods: Covalently tagged poly(lactic-co-glycolic) acid (PLGA) nanoparticles (PLGA-tetramethylrhodamine [PLGA-TRITC]), and PLGA-TRITC with entrapped coumarin-6 (double-tagged) nanoparticles, were synthesized using an oil-in-water emulsion evaporation method. Nanoparticle interaction with A. flavus was assessed using fluorescent microscopy.Results: PLGA-TRITC nanoparticles associated with the surface of fungal spores and hyphae, with limited fluorescence observed within the interior. With double-tagged nanoparticles, comparatively more red fluorescence (TRITC) was measured on the fungal surface and more green (coumarin-6) on the interior, resulting from uptake of released coumarin-6.Conclusion: The majority of nanoparticles associated with the fungal surface, while smaller nanoparticles were internalized. Surface association between polymeric nanoparticles and A. flavus may facilitate content uptake.